Boron nitride modified rubber composite material and preparation process thereof

By adding dibenzyl boron nitride and benzoyl peroxide to the rubber for chemical grafting reaction, the boron nitride modified rubber composite material is formed, which solves the problem of insufficient heat resistance and flame retardant properties of the rubber material, and achieves higher heat resistance and flame retardant properties.

CN119775647APending Publication Date: 2025-04-08SHENZHEN YUANFENGFENGYE TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510062991.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The poor heat resistance and flame retardant properties of existing rubber materials limit their applications in the fields of damping materials and tire manufacturing.

Method used

The rubber is added to the rubber to a chemical grafting reaction to form a boron nitride modified rubber composite material. The process includes introducing nitrogen-phosphorus synergistic flame retardants such as phosphate esters and phosphoramide on the surface of boron nitride, and chemically bonding the boron nitride to the rubber through hot pressing vulcanization technology.

Benefits of technology

The heat resistance and flame retardant properties of rubber are significantly improved, so that boron nitride can be evenly dispersed in the rubber matrix, delaying high-temperature decomposition and diffusion of combustion products, and at the same time enhancing the flame retardant properties of rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775647A_ABST
    Figure CN119775647A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new materials, and discloses a boron nitride modified rubber composite material and a preparation process thereof, phosphoryl chloride boron nitride reacts with 1, 2-bis (2-benzimidazolyl) ethylene to generate benzimidazole phosphoryl boron nitride, the benzimidazole phosphoryl boron nitride further reacts with hydroxyethyl dibenzyl phosphite to obtain phosphoric acid dibenzyl esterified benzimidazolyl boron nitride, and the phosphoric acid dibenzyl esterified benzimidazolyl boron nitride is further reacted with 1, 2-bis (2-benzimidazolyl) ethylene to obtain the boron nitride modified rubber composite material. According to the present invention, the boron nitride is introduced into the surface of the boron nitride, such that the abundant phosphate, phosphamide and other nitrogen-phosphorus synergistic flame retardants are introduced on the surface of the boron nitride, and the alkenyl functional group is contained in the structure, such that the graft copolymerization reaction with the rubber can be performed under the initiation of the initiator benzoyl peroxide so as to finally obtain the boron nitride modified rubber composite material, such that the heat resistance of the rubber is effectively enhanced; the nitrogen-phosphorus synergistic flame retardant grafted on the surface of the boron nitride can effectively enhance the flame retardant property of the rubber, and the phenomenon that the flame retardant property of the rubber is poor is greatly improved in cooperation with the excellent barrier property of the boron nitride.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, in particular to a boron nitride modified rubber composite material and a preparation process thereof. Background Art

[0002] Rubber has excellent properties such as elasticity, flexural resistance and tensile strength, and is widely used in fields such as national defense, military industry, transportation and medical care. Therefore, the requirements for its performance are becoming increasingly higher. However, rubber itself has poor heat resistance and weak flame retardancy, which greatly limits its application in damping materials and tire manufacturing. Therefore, in practical applications, it is basically necessary to modify the rubber and use organic or inorganic materials with excellent performance to fill the rubber matrix. This can greatly enhance the heat resistance and flame retardancy of the rubber, and has therefore been widely studied in recent years.

[0003] Boron nitride has excellent thermal conductivity and heat resistance, and is one of the nanomaterials frequently used in polymer heat resistance modification. In the "Performance Study of Boron Nitride Modified Polyurethane and Polyacrylic Acid Water-Based Flame-Retardant Cable Coating Materials", boron nitride was used with melamine phosphate and pentaerythritol to form a synergistic flame retardant to modify polyurethane and polyacrylic acid to be flame-retardant. Therefore, boron nitride can be used to modify polymer materials to be flame-retardant. However, boron nitride itself has poor compatibility with polymers and is often difficult to be evenly dispersed in the polymer material matrix without modification. Therefore, it is necessary to chemically bond small molecules with flame retardant and other functional properties to the surface of boron nitride through chemical grafting to increase its dispersibility and functionality, thereby reducing the difficulty of its application in polymer materials. Summary of the Invention

[0004] (1) Technical problems solved In view of the deficiencies of the prior art, the present invention provides a boron nitride modified rubber composite material and a preparation process thereof, which enhances the heat resistance and flame retardancy of the rubber.

[0005] (2) Technical solution To achieve the above object, the present invention provides the following technical solution: a boron nitride modified rubber composite material, the preparation process of which comprises the following steps: (1) Rubber was added to the torque rheometer and plasticized for 1-4 min. Then, dibenzyl phosphate-esterified benzimidazolyl boron nitride and benzoyl peroxide were added. After mixing evenly, the mixture was reacted at 130-160 °C for 4-12 min. The rotor speed was set to 50 r / min. The product was hot-pressed and vulcanized to obtain a boron nitride-modified rubber composite material.

[0006] Preferably, the mass proportions of the rubber are 100 parts, the mass proportions of dibenzyl phosphate-esterified benzimidazolyl boron nitride are 1-6.5 parts, and the mass proportions of benzoyl peroxide are 0.1-0.5 parts.

[0007] Preferably, the preparation process of the dibenzyl phosphate esterified benzimidazole boron nitride is as follows: (1) Using phosphorus oxychloride to modify the surface of boron nitride to obtain phosphoryl chloride boron nitride; (2) Adding phosphorylboron nitride chloride to an organic solvent, ultrasonically dispersing the mixture, and then adding 1,2-di(2-benzimidazole)ethylene and triethylamine. Mixing the mixture evenly, the mixture is transferred to an oil bath and reacted at 10-35°C for 6-18 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain benzimidazolephosphorylboron nitride. (3) Add 100 parts by mass of benzimidazole phospho-boron nitride to the ether solvent, disperse it evenly by ultrasonication, and then add 15-40 parts of hydroxyethyl dibenzyl phosphite (C 16 H 19 05P) and 20-55 parts of triethylamine, after stirring for 2-4 hours, continue to add 1.2-3.5 parts of 4-dimethylaminopyridine, mix well and transfer to an oil bath for reaction. After the reaction is completed, filter, wash and dry to obtain dibenzyl phosphate esterified benzimidazolyl boron nitride.

[0008] Preferably, the organic solvent in step (2) is any one of 1,2-dichloroethane, dichloromethane or chloroform.

[0009] Preferably, in step (2), the mass fractions of phosphoryl chloride boron nitride are 100 parts, 1,2-bis(2-benzimidazolyl)ethylene is 30-85 parts, and triethylamine is 1.5-4 parts.

[0010] Preferably, the reaction temperature in step (3) is 20-50° C. and the reaction time is 48-96 h.

[0011] (3) Beneficial technical effects Compared with the prior art, the present invention has the following beneficial technical effects: The boron nitride modified rubber composite material has hydroxyl groups on the surface of the boron nitride, which can react with some P-Cl bonds in the structure of phosphorus oxychloride to obtain phosphorus oxychloride boron nitride. Under the catalytic action of triethylamine, the P-Cl bonds in the structure can further react with the imino groups in the structure of 1,2-bis(2-benzimidazolyl)ethylene to generate benzimidazole phosphoryl boron nitride. The phosphoryl chloride group in the structure can further react with the hydroxyethyl group in the structure of hydroxyethyl dibenzyl phosphite to obtain dibenzyl phosphate-esterified benzimidazole boron nitride, thereby introducing abundant nitrogen-phosphorus synergistic flame retardants such as phosphate esters and phosphoramides onto the surface of the boron nitride. The alkenyl functional group in the structure can undergo a graft copolymerization reaction with the rubber under the initiation of benzoyl peroxide as an initiator. After hot pressing and vulcanization, the product finally obtains a boron nitride-modified rubber composite material, thereby connecting the boron nitride and the rubber in the form of a chemical bond, which greatly improves the interfacial performance between the boron nitride and the rubber, and enables the boron nitride to be more evenly dispersed in the rubber matrix. When the rubber is under high temperature conditions, the lamellar structure of the boron nitride can delay the diffusion of combustion products generated by the high-temperature decomposition of the rubber. At the same time, the presence of boron nitride can increase the cross-linking density of the rubber molecular chain, so that the movement of its molecular chain is restricted, thereby effectively enhancing the heat resistance of the rubber. The nitrogen-phosphorus synergistic flame retardant grafted on the surface of the boron nitride can effectively enhance the flame retardant properties of the rubber. Combined with the excellent barrier properties of boron nitride, it greatly improves the poor flame retardant properties of the rubber. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a schematic diagram of the synthesis of benzimidazolephosphoryl boron nitride.

[0013] Figure 2 This is a schematic diagram of the synthesis of benzimidazole boron nitride esterified with dibenzyl phosphate. DETAILED DESCRIPTION

[0014] To achieve the above objectives, the present invention provides the following embodiments and examples: A boron nitride modified rubber composite material, the preparation process of which is as follows: (1) Add boron nitride to chloroform solvent, mix well, then add triethylamine and phosphorus oxychloride, react at 10-30°C for 6-18 hours, and after treatment, obtain phosphoryl boron nitride chloride; (2) Add 100 parts by mass of phosphorylboron nitride chloride to any one of the organic solvents of 1,2-dichloroethane, dichloromethane or chloroform, and after ultrasonic dispersion, continue to add 30-85 parts of 1,2-di(2-benzimidazole)ethylene and 1.5-4 parts of triethylamine, mix well and transfer to an oil bath, react at 10-35°C for 6-18 hours, filter, wash and dry after the reaction to obtain benzimidazole phosphorylboron nitride; (3) Add 100 parts by mass of benzimidazole phospho-boron nitride to the ether solvent, disperse it evenly by ultrasonication, and then add 15-40 parts of hydroxyethyl dibenzyl phosphite (C 16 H 19 05P) and 20-55 parts of triethylamine, after stirring for 2-4 hours, continue to add 1.2-3.5 parts of 4-dimethylaminopyridine, mix well and transfer to an oil bath pot, react at 20-50 ° C for 48-96 hours, filter, wash and dry after the reaction to obtain dibenzyl phosphate esterified benzimidazolyl boron nitride; (4) Add 100 parts by mass of rubber to the torque rheometer, and after plasticizing for 1-4 minutes, continue to add 1-6.5 parts of dibenzyl phosphate-esterified benzimidazolyl boron nitride and 0.1-0.5 parts of benzoyl peroxide. After mixing evenly, react at 130-160°C for 4-12 minutes, set the rotor speed to 50 r / min, and hot-press vulcanize the product to obtain a boron nitride-modified rubber composite material. Example

[0015] (1) Add 0.2 g of boron nitride to 15 mL of chloroform solvent, mix well, then add 0.4 g of triethylamine and 2 g of phosphorus oxychloride, and react at 10 ° C for 6 h. After treatment, the product is obtained as phosphoryl boron nitride chloride; (2) Add 5 g of phosphorylboron nitride chloride to 50 mL of 1,2-dichloroethane solvent, disperse evenly by ultrasonication, then add 1.5 g of 1,2-di(2-benzimidazole)ethylene and 0.075 g of triethylamine, mix evenly and transfer to an oil bath, react at 10 ° C for 6 h, filter, wash and dry after the reaction to obtain benzimidazole phosphorylboron nitride; (3) Add 1g of benzimidazole phospho-boron nitride to 30mL of ether solvent, disperse it evenly by ultrasonication, and then add 0.15g of hydroxyethyl dibenzyl phosphite (C 16 H 19 05P) and 0.2g triethylamine, after stirring for 2h, continue to add 0.012g 4-dimethylaminopyridine, mix well and transfer to an oil bath pot, react at 20°C for 48h, filter, wash and dry after the reaction to obtain dibenzyl phosphate esterified benzimidazolyl boron nitride; (4) Add 10 g of rubber to the torque rheometer and plasticize for 1 min. Then, add 0.1 g of dibenzyl phosphate-esterified benzimidazolyl boron nitride and 0.01 g of benzoyl peroxide. After mixing evenly, react at 130 °C for 4 min. Set the rotor speed to 50 r / min. After hot pressing and vulcanization, the product is obtained to obtain a boron nitride-modified rubber composite material. Example

[0016] (1) Add 0.2 g of boron nitride to 20 mL of chloroform solvent, mix well, then add 0.45 g of triethylamine and 2.5 g of phosphorus oxychloride, and react at 15 ° C for 12 h. After treatment, the product is obtained as phosphoryl boron nitride chloride; (2) Add 5 g of phosphorylboron nitride chloride to 60 mL of dichloromethane solvent, disperse evenly by ultrasonication, then add 2.5 g of 1,2-di(2-benzimidazolyl)ethylene and 0.1 g of triethylamine, mix evenly and transfer to an oil bath, react at 20 ° C for 8 h, filter, wash and dry after the reaction to obtain benzimidazole phosphorylboron nitride; (3) Add 1g of benzimidazole phospho-boron nitride to 40mL of ether solvent, disperse it evenly by ultrasonication, and then add 0.25g of hydroxyethyl dibenzyl phosphite (C 16 H 19 05P) and 0.3g triethylamine, after stirring for 3h, continue to add 0.02g 4-dimethylaminopyridine, mix well and transfer to an oil bath pot, react at 30°C for 60h, filter, wash and dry after the reaction to obtain dibenzyl phosphate esterified benzimidazolyl boron nitride; (4) Add 10 g of rubber to the torque rheometer and plasticize for 2 min. Then, add 0.3 g of dibenzyl phosphate-esterified benzimidazolyl boron nitride and 0.02 g of benzoyl peroxide. After mixing evenly, react at 140 °C for 6 min. Set the rotor speed to 50 r / min. After hot pressing and vulcanization, the product is obtained to obtain a boron nitride-modified rubber composite material. Example

[0017] (1) Add 0.4 g of boron nitride to 60 mL of chloroform solvent, mix well, then add 1 g of triethylamine and 6 g of phosphorus oxychloride, react at 20 ° C for 16 h, and the product is treated to obtain phosphoryl boron nitride chloride; (2) Add 10 g of phosphorylboron nitride chloride to 160 mL of chloroform solvent, disperse evenly by ultrasonication, then add 7 g of 1,2-di(2-benzimidazolyl)ethylene and 0.3 g of triethylamine, mix evenly and transfer to an oil bath, react at 30 ° C for 12 h, filter, wash and dry after the reaction to obtain benzimidazole phosphorylboron nitride; (3) Add 2g of benzimidazole phospho-boron nitride to 100mL of ether solvent, disperse it evenly by ultrasonication, and then add 0.7g of hydroxyethyl dibenzyl phosphite (C 16 H 19 05P) and 0.8g triethylamine, stirred for 3h, then added 0.06g 4-dimethylaminopyridine, mixed evenly and transferred to an oil bath, reacted at 40°C for 72h, filtered, washed and dried to obtain dibenzyl phosphate esterified benzimidazolyl boron nitride; (4) Add 20 g of rubber to the torque rheometer and plasticize for 3 min. Then, add 1 g of dibenzyl phosphate-esterified benzimidazolyl boron nitride and 0.08 g of benzoyl peroxide. After mixing evenly, react at 150 °C for 8 min. Set the rotor speed to 50 r / min. After hot pressing and vulcanization, the product is obtained to obtain a boron nitride-modified rubber composite material. Example

[0018] (1) Add 0.2 g of boron nitride to 40 mL of chloroform solvent, mix well, then add 0.6 g of triethylamine and 4 g of phosphorus oxychloride, react at 30 ° C for 18 h, and the product is treated to obtain phosphoryl boron nitride chloride; (2) Add 5 g of phosphorylboron nitride chloride to 100 mL of 1,2-dichloroethane solvent, disperse evenly through ultrasonication, then add 4.25 g of 1,2-di(2-benzimidazole)ethylene and 0.2 g of triethylamine, mix evenly, transfer to an oil bath, and react at 35 °C for 18 h. After the reaction is complete, filter, wash, and dry to obtain benzimidazole phosphorylboron nitride; (3) Add 1g of benzimidazole phospho-boron nitride to 60mL of ether solvent, disperse it evenly by ultrasonication, and then add 0.4g of hydroxyethyl dibenzyl phosphite (C 16 H 19 05P) and 0.55g triethylamine, after stirring for 4h, continue to add 0.035g 4-dimethylaminopyridine, mix well and transfer to an oil bath pot, react at 50°C for 96h, filter, wash and dry after the reaction to obtain dibenzyl phosphate esterified benzimidazolyl boron nitride; (4) Add 10 g of rubber to the torque rheometer and plasticize for 4 min. Then, add 0.65 g of dibenzyl phosphate-esterified benzimidazolyl boron nitride and 0.05 g of benzoyl peroxide. After mixing evenly, react at 160 °C for 12 min. Set the rotor speed to 50 r / min. After hot pressing and vulcanization, the product is obtained to obtain a boron nitride-modified rubber composite material.

[0019] Comparative Example 1 (1) Add 0.2 g of boron nitride to 15 mL of chloroform solvent, mix well, then add 0.4 g of triethylamine and 2 g of phosphorus oxychloride, and react at 10 ° C for 6 h. After treatment, the product is obtained as phosphoryl boron nitride chloride; (2) Add 5 g of phosphorylboron nitride chloride to 50 mL of 1,2-dichloroethane solvent, disperse evenly by ultrasonication, then add 1.5 g of 1,2-di(2-benzimidazole)ethylene and 0.075 g of triethylamine, mix evenly and transfer to an oil bath, react at 10 ° C for 6 h, filter, wash and dry after the reaction to obtain benzimidazole phosphorylboron nitride; (3) Add 10 g of rubber to the torque rheometer and plasticize for 1 min. Then, add 0.1 g of benzimidazole phospho-boron nitride and 0.01 g of benzoyl peroxide. Mix well and react at 130 °C for 4 min. Set the rotor speed to 50 r / min. After hot pressing and vulcanization, the product is obtained to obtain a boron nitride-modified rubber composite material.

[0020] Comparative Example 2 (1) Add 0.2 g of boron nitride to 40 mL of chloroform solvent, mix well, then add 0.6 g of triethylamine and 4 g of phosphorus oxychloride, react at 30 ° C for 18 h, and the product is treated to obtain phosphoryl boron nitride chloride; (2) 10 g of rubber and 0.65 g of boron nitride phosphate chloride were added to the torque rheometer, and after plasticizing for 4 min, the mixture was hot-pressed and vulcanized to obtain a boron nitride-modified rubber composite material.

[0021] In a nitrogen atmosphere, the initial decomposition temperatures of the composite materials in the examples and comparative examples were tested using a TGA-601 thermogravimetric analyzer. The test temperature was 25-600° C., and the heating rate was 10° C. / min.

[0022] project Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Initial decomposition temperature (℃) 337.2 344.1 348.9 345.8 330.5 336.4 The heat release rate and peak heat release rate of the composite materials in Examples and Comparative Examples were tested using a PX-07-007 cone calorimeter.

[0023] project Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 <![CDATA[Total heat release (MJ / m 2 )]]> 124.5 101.6 109.1 132.9 139.2 156.8 <![CDATA[Peak heat release rate (kW / m 2 )]]> 661.5 428.1 369.8 411.0 465.9 1038.3 Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A process for preparing a boron nitride modified rubber composite material, characterized in that: The preparation process comprises the following steps: (1) Add rubber to the torque rheometer, and after plasticizing for 1-4 minutes, continue to add dibenzyl phosphate esterified benzimidazole boron nitride and benzoyl peroxide, mix well, react at 130-160°C for 4-12 minutes, set the rotor speed to 50 r / min, and obtain the boron nitride modified rubber composite material after hot pressing and vulcanization of the product.

2. The process for preparing a boron nitride modified rubber composite material according to claim 1, characterized in that: The mass proportion of the rubber is 100 parts, the mass proportion of dibenzyl phosphate esterified benzimidazole boron nitride is 1-6.5 parts, and the mass proportion of benzoyl peroxide is 0.1-0.5 parts.

3. The process for preparing a boron nitride modified rubber composite material according to claim 1, characterized in that: The preparation process of the dibenzyl phosphate esterified benzimidazole boron nitride is as follows: (1) Using phosphorus oxychloride to modify the surface of boron nitride to obtain phosphoryl chloride boron nitride; (2) Adding phosphoryl chloride boron nitride to an organic solvent, and after ultrasonic dispersion, continuing to add 1,2-di(2-benzimidazole)ethylene and triethylamine, mixing evenly, transferring to an oil bath, reacting at 10-35°C for 6-18h, filtering, washing and drying after the reaction to obtain benzimidazole phosphoryl boron nitride; (3) Add 100 parts by weight of benzimidazole phospho-boron nitride to the ether solvent, disperse it evenly by ultrasonication, and then add 15-40 parts of hydroxyethyl dibenzyl phosphite (C 16 H 19 After stirring for 2-4 hours, 1.2-3.5 parts of 4-dimethylaminopyridine are added, mixed evenly and transferred to an oil bath for reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain dibenzyl phosphate esterified benzimidazole boron nitride.

4. The process for preparing a boron nitride modified rubber composite material according to claim 3, characterized in that: The organic solvent in step (2) is any one of 1,2-dichloroethane, dichloromethane or chloroform.

5. The process for preparing a boron nitride modified rubber composite material according to claim 3, characterized in that: In the step (2), the mass fractions of phosphoryl chloride boron nitride are 100 parts, 1,2-di(2-benzimidazolyl)ethylene is 30-85 parts, and triethylamine is 1.5-4 parts.

6. The process for preparing a boron nitride modified rubber composite material according to claim 3, characterized in that: The reaction temperature in step (3) is 20-50°C and the reaction time is 48-96h.

Citation Information

Patent Citations

  • Ceramic boron-containing doping paste and methods therefor

    CN103649011A

  • Graphene-natural rubber composite toughened and modified polylactic acid film and preparation method thereof

    CN113754909A

  • Nitrogen-phosphorus synergistic flame-retardant functional montmorillonite modified PVC wood-plastic plate and preparation method thereof

    CN114196129A

  • High-thermal-conductivity epoxy resin composition based on copper-clad plate and preparation method of high-thermal-conductivity epoxy resin composition

    CN118725518A

  • Flame retardant composition, flame retardant resin composition containing said flame retardant composition, and molded body of said flame retardant resin composition

    WO2019065518A1